2015
DOI: 10.1002/2014jc010678
|View full text |Cite
|
Sign up to set email alerts
|

A basal stress parameterization for modeling landfast ice

Abstract: Current large-scale sea ice models represent very crudely or are unable to simulate the formation, maintenance and decay of coastal landfast ice. We present a simple landfast ice parameterization representing the effect of grounded ice keels. This parameterization is based on bathymetry data and the mean ice thickness in a grid cell. It is easy to implement and can be used for two-thickness and multithickness category models. Two free parameters are used to determine the critical thickness required for large i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(122 citation statements)
references
References 29 publications
(84 reference statements)
4
114
0
Order By: Relevance
“…This will be tested in the upcoming future. Second, a landfast ice parametrization (Lemieux et al, 2015b) should improve the representation of ice dynamics over the shelves, especially on the Siberian side, and we are hopeful for results in the very near future in this area as well. Third, two-way coupling of the wave field, the ocean and the ice is in progress (Dumont et al, 2011) and is expected to improve substantially the upper ocean response (with the addition of Stokes currents and induced mixing), the representation of the ice in the marginal ice zone and the wave field in general.…”
Section: Discussionmentioning
confidence: 99%
“…This will be tested in the upcoming future. Second, a landfast ice parametrization (Lemieux et al, 2015b) should improve the representation of ice dynamics over the shelves, especially on the Siberian side, and we are hopeful for results in the very near future in this area as well. Third, two-way coupling of the wave field, the ocean and the ice is in progress (Dumont et al, 2011) and is expected to improve substantially the upper ocean response (with the addition of Stokes currents and induced mixing), the representation of the ice in the marginal ice zone and the wave field in general.…”
Section: Discussionmentioning
confidence: 99%
“…A pan‐Arctic ice‐ocean model is used to conduct two 10‐year simulations (1 October 2001 to 31 December 2010): one with no tides , referred to as NT, and one with tides , referred to as T. The sea ice model is CICE version 4.0 (Hunke & Lipscomb, ) with some modifications that include the UK Met Office CICE‐NEMO interface (Megann et al, ), the grounding scheme of Lemieux et al (), and a modified VP rheology as described in Lemieux et al (). Including the seabed stress as in Lemieux et al (), the sea ice momentum equation becomes mnormalDuinormalDt=boldk×mfui+bold-italicτa+bold-italicτo+bold-italicτb+bold-italic∇·bold-italicσmgbold-italic∇Ho, where m is the combined mass of ice and snow per unit area; DnormalDt is the total derivative; t is the time; f is the Coriolis parameter; u i = u i i + v i j is the horizontal sea ice velocity vector; i , j , and k are unit vectors aligned with the x , y , and z axis of the coordinate system; τ a = τ a x i + τ a y j is the atmospheric stress; τ o = τ o x i + τ o y j is the ocean stress; τ b = τ b x i + τ b y j is the seabed (or basal) stress term due to grounded ridges; ∇ · σ is referred to as the rheology term with σ the internal ice stress tensor with components given by σ 11 = σ x x , σ 22 = σ y y , and σ 12 = σ x y ; g is the gravity; and H o the sea surface height.…”
Section: Methodsmentioning
confidence: 99%
“…In the Laptev Sea, grounded pressure ridges have been observed and identified as anchor points for the stabilization of the landfast ice cover (Haas et al, ; Selyuzhenok et al, ). Modeling experiments suggest that grounding is also an important mechanism for the presence of landfast ice in the East Siberian Sea (Lemieux et al, , ). As the Kara Sea is overall deeper than the East Siberian and Laptev Seas, grounding is less effective and it is thought that a series of islands act as pinning points for stabilizing its landfast ice cover (Divine et al, ; Olason, ).…”
Section: Introductionmentioning
confidence: 99%
“…For climate studies and forecasting purposes a more sophisticated parametrization is needed to capture long-term and seasonal changes in the fast-ice zone. Modeling of the fast-ice zone has received relatively little attention, but recent studies (Lemieux et al, 2015;Olason, 2016) have suggested new ways to parametrize the fast-ice zone, which could be feasible for a Baltic Sea ice model.…”
Section: Daily Sea-ice Extent and Thickness For Two Extreme Wintersmentioning
confidence: 99%